2013
DOI: 10.1097/igc.0b013e31829703b0
|View full text |Cite
|
Sign up to set email alerts
|

The Need for More Workshops in Laparoscopic Surgery and Surgical Anatomy for European Gynaecological Oncology Trainees

Abstract: This report for the first time highlights the relative importance and significance European trainees attach to some of their training needs in gynecologic oncology. Laparoscopic surgery, surgical anatomy, and imaging appear to be the 3 areas of greatest need. The European Society of Gynaecological Oncology, other national specialist societies, and institutions should direct additional training efforts at these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Ovarian cancer is the cause of greatest number of cancer-related deaths worldwide according to the latest statistical data, with high mortality rate due to the asymptomatic profile in early stages and nonsensitive diagnostic methods. 7 9 Ovarian cancer is frequently diagnosed in final stages when massive ascites and peritoneal spreading has already occurred, a stage that usually is nonresponsive to classic but to aggressive treatment methods, 10 and the survival rate remains low at 30%. 8 , 11 In this regard, there is an urgent need not only for more sensitive and precise diagnostic methods but also for methods that are able to discriminate this type of malignant pathology in the early stages of development, or more preferably, before the installation of this asymptomatic disease, in the form of prevention biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is the cause of greatest number of cancer-related deaths worldwide according to the latest statistical data, with high mortality rate due to the asymptomatic profile in early stages and nonsensitive diagnostic methods. 7 9 Ovarian cancer is frequently diagnosed in final stages when massive ascites and peritoneal spreading has already occurred, a stage that usually is nonresponsive to classic but to aggressive treatment methods, 10 and the survival rate remains low at 30%. 8 , 11 In this regard, there is an urgent need not only for more sensitive and precise diagnostic methods but also for methods that are able to discriminate this type of malignant pathology in the early stages of development, or more preferably, before the installation of this asymptomatic disease, in the form of prevention biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…A major weakness is the low response rate to this survey, even though it is comparable with other questionnaire-based surveys 24,25 and even slightly higher than the previous ENYGO survey. 1 The results may, therefore, not be representative of all ENYGO members. The results may, for the same reason, be prone to selection bias, because members who do not use SM would be unlikely to respond to this survey.…”
Section: Discussionmentioning
confidence: 98%
“…However, the previous study indicated similar educational needs irrespective of training program and country. 1 In summary, this survey provided valuable information on the pattern of SM use among the ENYGO members and initiated the ENYGO Facebook page. Using SM for clinical discussion will require specific guidelines to secure professional and consumer integrity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 As American and European trainees have requested, we emphasize the need for further training in minimally invasive surgery. 7,8 In addition, there is clear evidence, that at least in advanced ovarian cancer, formal surgical training positively influences the survival of patients. 9Y13 Meanwhile, the surgical training in ovarian cancer among members of our society is quite heterogeneous, 14 even among gynecological oncologists in countries with a long history of subspecialty training.…”
Section: Discussionmentioning
confidence: 99%